Integrative analysis of lysine acetylation-related genes and identification of a novel prognostic model for oral squamous cell carcinoma - Deng, Shi-Zhou; Wu, Xuechen; Tang, Jiezhang; Dai, Lin; Cheng, Bo (Frontiers in Molecular Biosciences, 2023)
Oral squamous cell carcinoma (OSCC), which accounts for a high proportion of oral cancers, is characterized by high aggressiveness and rising incidence. Lysine acetylation is associated with the pathogenesis of cancer pathogenesis. Lysine acetylation-related genes (LARGs) are a treatmenttherapeutic targets and possibletential prognostic indicators in various for many kinds of tumors, including OSCC. However, the systematic bioinformatics analysis of the LARGs in OSCC is still unexplored. Here, we analyzed the expression of 33 LARGs in OSCC and the effects of their somatic mutations on OSCC prognosis. Consistent clustering analysis identified two lysine acetylation patterns and the differences between the two patterns were further evaluated. Least absolute shrinkage and selection operator (LASSO) regression analysis was used to createdevelop a lysine acetylation-related prognostic model usingin TCGA OSCC datasets, which was laterthen validated using gene expression omnibus (GEO) dataset in GSE41613. Patients with lower risk scores had a better prognoseis, in both the overall cohort and within the subgroups. These patients also had "hot" immune microenvironments and were more sensitive to immunotherapy. Our findings offer a new model for classifying OSCC and determining its prognosis and also offer novel insights into OSCC diagnosis and treatment.